Cosmic Strings in an Open Universe with Baryonic and Non-Baryonic Dark Matter - Ferreira, P (1994)
We study the effects of cosmic strings on structure formation in open universes. We calculate the power spectrum of density perturbations for two class of models: one in which all the dark matter is non baryonic (CDM) and one in which it is all baryonic (BDM). Our results are compared to the 1 in 6 IRAS QDOT power spectrum. The best candidates are then used to estimate $μ$, the energy per unit length of the string network. Some comments are made on mechanisms by which structures are formed in the two theories.